Design and Development of Bionic Eye for Visually Challenged People using Raspberry Pi Processor (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Bionic Eye will play a major role in the future development of visually challenged people. This research focuses on design and development of Bionic Eye to detect the hurdles for visually challenged people. This intelligence system uses the shape and movement of an object for detection and tracking. The object recognition rate is improved with the help of Stochastic Decent Gradient algorithm. Raspberry Pi is the processor used for the Bionic Eye as it gives out command on the object detection and the data from the camera is collected and then transmitted to the system. The distance and object movement is obtained by ultrasonic sensor. The range of the ultrasonic sensor is set and the distance is measured. A camera is used for capturing the object. A voice output saying “there is an object in front of you” is heard after an object is detected. The accuracy of the object detection is obtained by the deep learning algorithm. Increasing the recognition rate is the main advantage over object detection systems